The Court of Justice of the European Union and fixed-term work: Putting a brake on labour market dualization?. (July 2017) - de la Porte, Caroline; Emmenegger, Patrick
While fixed-term work benefits employers and increases the prospects of employability of various categories of workers, it is inherently precarious. The European Union (EU) directive on fixed-term work emphasizes the importance of equal treatment of workers on fixed-term contracts with comparable permanent workers and aims to prevent abuse of this contract form. Surprisingly, the Court of Justice of the European Union (CJEU) rulings in this area have by and large been neglected in comparative labour market research. We fill this gap by systematically analysing the CJEU case law concerning fixed-term work and connecting it to the literatures on labour market dualization and Europeanization of labour law. We develop an analytical framework to analyse the Europeanization of labour law, which we then use to analyse the directive and the case law regarding the directive on fixed-term work. Our findings show that the equal treatment is affirmed in all cases under analysis for different provisions of labour contracts. With regard to abuse of recourse to fixed-term contracts, by contrast, the rulings still represent a zone of legal uncertainty, whereby some judgments allow for fixed-term contracts, such as for social policy purposes, while others prohibit their use. We therefore conclude that the CJEU does not put a brake on labour market dualization, but it does insist on equal treatment of workers, regardless of their contractual arrangements.